Magnetostrictive vibrational power generator for battery-free IoT application - Toshiyuki Ueno (AIP Advances, 2019)
This study proposes a novel vibrational power generator based on magnetostrictive material (Fe–Ga alloy) for battery-free Internet of Things (IoT) applications. The device consists of a U-shaped magnetic frame with one leg forming a unimorph comprising a bonded Fe–Ga alloy plate and magnetic material, with a coil wound over the unimorph and a permanent magnet placed between the two legs of the frame. Via magnetically saturating the part of the frame at the point where the Fe–Ga plate is bonded, an electromotive force is generated in the coil by vibrations according to the change in the magnetic flux of the Fe–Ga alloy as generated by the inverse magnetostrictive effect. The device is simple in structure, highly robust, and affords an ease of assembling that is suitable for mass production. We also evaluate a prototype device (device weight of 4 g) using an Fe–Ga plate with dimensions of 4 × 0.5 × 16 mm. With a weight of 1.7 g attached to the device, an open-circuit voltage of 4 V at an oscillation frequency of 88.7 Hz and acceleration of 6.0 m/s2 yields an effective power of 2.0 mW. With a weight of 10.2 g, an effective power of 0.39 mW is generated at a frequency of 28.4 Hz and acceleration of 0.73 m/s2. After 100 million repeated oscillations at 420 Hz and 78.4 m/s2, the resonant frequency and voltage remain unchanged. The device performance is sufficient to replace the button cell used in wireless modules. Further, in order to examine the device feasibility, I investigate two applications related to short-distance (sending ON signals) and long-distance (sending data of temperature and vibration frequency) wireless sensors driven by the proposed device.